Pandemi Covid-19 dan Pengaruhnya pada Permintaan dan Penawaran Emas di Indonesia - Edo Kurniawan; Usman Bustaman (Seminar Nasional Official Statistics, 2022)
The demand for gold during the pandemic has decreased drastically compared to before the pandemic. The Large-Scale Social Restrictions (PSBB) implemented by the Indonesian government indirectly also reduced the gold supply. This study aims to analyze the effect of the Covid-19 pandemic on the demand and supply of gold in Indonesia. By using a simultaneous equation model, the effect of the Covid-19 pandemic is expressed in three structural equations, namely as an exogenous variable that affects demand (model 1) or supply (model 2) and as an endogenous variable (model 3). The estimation results using two stage least squares show that the Covid-19 pandemic has a negative effect on gold supply (in model 2) and a positive effect on gold demand (in model 3). Given the impact of the pandemic, it was found that gold investment and jewelry had a positive effect on gold demand, while gold prices, previous quarter gold prices, and growth in gold reserves had a positive effect on gold supply.